2019
DOI: 10.20947/s102-3098a0068
|View full text |Cite
|
Sign up to set email alerts
|

Os processos de urbanização e conversão florestal na Amazônia paraense – um estudo multiescalar

Abstract: Na Amazônia brasileira, as dinâmicas de urbanização e conversão florestal possuem lógicas complexas, dependentes de fatores e agentes atuando em diferentes escalas. Este artigo explora a evolução espacial e temporal da urbanização e da conversão florestal na Amazônia, a partir de elementos mensuráveis presentes nestes processos: a expansão urbana, dimensão observável dos processos de urbanização; e o desmatamento, uma medida dos processos de conversão florestal. A identificação de padrões espaço-temporais simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Deforestation analysis of the municipalities of the Sustainable Forests District of BR-163 4 showed that urban dynamics directly reflects in deforestation rates, but considering the heterogeneity of the study area, it is not possible to establish a causal relationship (DAL´ASTA et al, 2012). Seeking space-time patterns of urbanization and deforestation in the state of Pará, a multiscale study reaffirmed the complexity of establishing conclusive relationships between these two phenomena (RIBEIRO et al, 2019).…”
Section: Deforestation and Urbanization: A Systematic Literature Reviewmentioning
confidence: 90%
“…Deforestation analysis of the municipalities of the Sustainable Forests District of BR-163 4 showed that urban dynamics directly reflects in deforestation rates, but considering the heterogeneity of the study area, it is not possible to establish a causal relationship (DAL´ASTA et al, 2012). Seeking space-time patterns of urbanization and deforestation in the state of Pará, a multiscale study reaffirmed the complexity of establishing conclusive relationships between these two phenomena (RIBEIRO et al, 2019).…”
Section: Deforestation and Urbanization: A Systematic Literature Reviewmentioning
confidence: 90%
“…Forest loss in the Neotropical region, especially in Amazonian rainforests, has been increasing at alarming rates in the last decades mostly due to the agricultural expansion and the exploration of natural resources (e.g., mining activity) (Fearnside 2005;Sonter et al 2017;Ribeiro et al 2019). Anthropogenic activities in the Amazon have demanded an increase in infrastructure causing direct and indirect environmental shifts in the region due to the establishment and expansion of urban centers (Sonter et al 2017;Cortês and Silva Jr, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Didelphimorphia,Rodentia,armadilhas,rim,fígado,16S rRNA Leptospirosis is a globally distributed zoonosis and is known to have domestic and wild animal species as reservoirs, mainly small mammals such as rodents and marsupials (Adler and De La Peña Moctezuma 2010). In the Brazilian Amazon, the intensification of land demand generates the emergence and expansion of urban borders, contributing to the increase in deforestation (Ribeiro et al 2018). Deforestation generates environmental changes and ecological disturbances that facilitate contact with wild species, favoring the incidence of diseases transmitted by animals (Saccaro Junior et al 2015).…”
mentioning
confidence: 99%